Generative Integration of AI for the Education of Islamic Communication and Broadcasting Students - Fujiantie, Jerina; Hartati, Rahmi (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2024)
Generative AI is one of the forms of AI used by people today. In the field of education, the use of Generative AI turns out to pose various challenges. This study aims to explore how Generative AI is used in lectures, describe changes in learning culture and the impact of using Generative AI, and provide suggestions on how to optimize the integration of Generative AI for Communication and Islamic Broadcasting students of UIN Antasari Banjarmasin. This study involved lecturers and students as research subjects. The data collection techniques used were in-depth interviews and documentation. The results showed that students of the Islamic Communication and Broadcasting (KPI) Study Program at UIN Antasari Banjarmasin use Generative AI to fulfill lecture assignments. The use of Generative AI by KPI UIN Antasari students causes changes in the culture and style of lectures. Students are more active in asking questions and discussing. Generative AI integration also has negative impacts, such as students lacking literacy and critical thinking skills. Students also have to face various challenges with the use of Generative AI. To overcome these challenges and impacts, the use of Generative AI must be optimized. Starting from the role of guidance and direction from lecturers, training in the use of AI, and the need for policies that result in the collaboration of traditional learning culture and modern learning using Generative AI for student education.